Determination of Clinical Profile of Childhood Extrapulmonary Tuberculosis - Dhara K. Gosai; Jigar B. Gosai; Omprakash S. Shukla (Recent Developments in Medicine and Medical Research Vol. 8, 2021)
Background: Tuberculosis is the world’s second leading cause of death from an infectious disease, being second only to AIDS. There is a lack of good data on the prevalence of all types of tuberculosis among children in India; most surveys have focused on pulmonary tuberculosis. The current study aimed to investigate the clinical profile of various types of childhood EPTB. The current study sought to investigate the clinico-epidemiological profile of various forms of childhood EPTB. Objectives: To observe the agewise distribution of various forms of extrapulmonary tuberculosis in children and to analyse demographic profile and different clinical presentations of childhood extrapulmonary tuberculosis . Methods: Retrospective analysis of clinical profile of 100 patients of childhood EPTB in the age group of 6 months to 12 years. Results: In our study, 62 percent of the cases were aged 0-5 years, 38 percent were aged 5-12 years (P = 0.041), with a male to female ratio of 1.9:1. 96 percent (P = 0.016) of the patients belonged to the lower socioeconomic class (P = 0.01). The distribution of EPTB was - TBME (46%), disseminated TB (21%), pleural effusion (12%), abdominal TB (10%), TB lymphadenitis (7%), Osteoarticular (4%). 28% of the patients had mild to moderate malnutrition (PEM Grade-I,II) and 46% (PEM Grade-III,IV) were severely malnourished. 66% of the patient were BCG vaccinated & history of Koch’s contact were present in 28% of the all cases. Fever was present in 97 percent of CNS tuberculosis patients, followed by altered sensorium and convulsion in 80%, tonic posturing in 60%, and abnormal movements in 4%. The most common sign was tonic posturing in 60%, with the crack pot sign positive in 41%. Fever (100%), anorexia (90%), weight loss (80%), abdominal pain (50%), and hepatomegaly were common findings in 100% of cases of abdominal tuberculosis. Conclusion: Childhood EPTB is most common in children over the age of one year, those from lower socioeconomic classes, and those who are severely malnourished. CNS tuberculosis is characterised by fever, altered sensorium, convulsions, and abnormal movements, whereas abdominal tuberculosis is characterised by fever, anorexia, weight loss, and abdominal pain.